The Herodotus Paradox - Michael R. Baye; Dan Kovenock; Casper G. de Vries (Center for Economic Studies and ifo Institute (CESifo), 2010)
The Babylonian bridal auction, described by Herodotus, is regarded as one of the earliest uses of an auction in history. Yet, to our knowledge, the literature lacks a formal equilibrium analysis of this auction. We provide such an analysis for the two-player case with complete and incomplete information, and in so doing identify what we call the 'Herodotus Paradox.'
Keywords: C72; D44; 330; Auktionstheorie; Informationsökonomik; Spieltheorie; Gleichgewicht; Theorie